2017
DOI: 10.1111/nmo.13099
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the pre‐ and postpeak phases in a swallow using esophageal pressure topography

Abstract: Background and aim The current paradigm of measuring esophageal contractile vigor assesses the entirety of a pressure wave using a single measurement, the distal contractile integral (DCI). We hypothesize that an assessment identifying separate phases of the contractile pressure wave before and after the pressure peak may help distinguish abnormalities in patients presenting with chest pain and dysphagia. The aim of the present study was to develop a technique to assess the individual phases and report on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The success rates of both the length > 10 cm, and the length < 10 cm were 91.1% and 89.1%, respectively[21]. There are several researches on the symptom in patients with Jackhammer esophagus and the pre-peak and post-peak phase of contraction[3,22]. In these regards, to distinguish the contractile integral components of pre-peak and post peak phase contractile activity is important to treat Jack hammer disease[3,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success rates of both the length > 10 cm, and the length < 10 cm were 91.1% and 89.1%, respectively[21]. There are several researches on the symptom in patients with Jackhammer esophagus and the pre-peak and post-peak phase of contraction[3,22]. In these regards, to distinguish the contractile integral components of pre-peak and post peak phase contractile activity is important to treat Jack hammer disease[3,22].…”
Section: Discussionmentioning
confidence: 99%
“…There are several researches on the symptom in patients with Jackhammer esophagus and the pre-peak and post-peak phase of contraction[3,22]. In these regards, to distinguish the contractile integral components of pre-peak and post peak phase contractile activity is important to treat Jack hammer disease[3,22]. However, there are still concerns regarding post-POEM complications for medication refractory Jackhammer esophagus after POEM, such as passage disturbance and sigmoid esophagus[2,11-14].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we tried a new measurement tool, where the up-and down-slope of the peristaltic wave were separated in order to make a more detailed measurement for both the contraction and relaxation phases of contraction. 7 Using this new algorithm, we found that the abnormalities in contractile integral of the post-peak phase are more significant in jackhammer esophagus patients with higher dysphagia scores. 8 This approach may have masked the abnormalities in the swallows with persistent repetitive contraction peaks since only the first peak was analyzed in this new approach.…”
Section: Introductionmentioning
confidence: 88%
“…HRM procedure was performed as previously described. 7 The esophageal pressure topography was analyzed using the Manoview analysis software incorporated by the manufacturer (Medtronic Inc. Minneapolis, MN, USA). The DCI, distal latency (DL) as well as integrated relaxation pressure (IRP) of the supine liquid swallows were analyzed among all the jackhammer patients.…”
Section: High-resolution Manometrymentioning
confidence: 99%
“…Recently, we assessed the pre-and post-peak contractile activity in a group of jackhammer patients and asymptomatic controls and found that increased post-peak contractile activity was associated with dysphagia symptom severity and that this was mostly related to prolonged post-peak contraction and not an overt difference in contraction strength measured by DCI. These finding suggest that although this motor pattern is primarily considered to be a hypercontractle motor disorder, there are also abnormalities in propagation and post-peak return of the muscle fibers to their low-tension state and length (4)(5). We theorized that this could be related to an imbalance in the excitatory and inhibitory activity related to defects in the intrinsic myogenic contractile apparatus or a defect in the input from the enteric and central nervous system.…”
Section: Introductionmentioning
confidence: 99%